Who are the veterinary students of New Zealand?, &, do the demographic characteristics and attitudes of veterinary students influence the behaviour of dogs : thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Studies in Animal Behaviour at Massey University, Palmerston North, New Zealand - Coombes, Rebecca Hean (Massey University, 2004)
Internationally the veterinary profession has been enduring a period of change. There has been an increase in women, an increase in small animal practices and a diversification of skills required to be a successful veterinary professional. This research attempts to answer several key questions raised by these changes: What is the demography, attitude, and experience of New Zealand veterinary students? Will any of these characteristics influence the behaviour of their canine patients? The research was divided into two studies. Study one investigated the veterinary students attending Massey University in 1999. The questionnaire administered to 261 veterinary students found 66% of students were female, 75% had owned a dog, 86% are from New Zealand, 67% lived in suburban or urban areas and 31% had attended tertiary education prior to commencing the veterinary degree. Students in the later years of the degree were less likely to have had prior tertiary education. These figures demonstrate a clear shift in demographics of veterinary students that reflects international trends. In addition, the Pet Attitude Scale was modified to specifically measure veterinary students' attitudes to dogs. The average attitude towards dogs was positive, the range and distribution were normal. Females and dog owners had significantly more positive attitudes to dogs. No other variable had significant differences in attitudes towards dogs. Study two looked at the influence of the demographic characteristics and attitudes of the veterinary students on the behaviour of dogs. The study consisted of a questionnaire and observation of a practical exercise. A golden retriever and a German shepherd were used for the practical exercise, all participants completed manoeuvres with both dogs. Aspects of the dogs' behaviour were used to calculate a submission result. The German shepherd had a significantly lower submission result than the golden retriever. The study found no significant differences in gender, attitude towards dogs, the participants' confidence in handling dogs, fear of unknown dogs, previous medical treatment for a dog bite, experience working with dogs or dog ownership when compared with the submission result. However, females did take significantly longer to complete the practical exercise. There are implications to the veterinary profession given the greater percentage of females entering veterinary science in New Zealand. Females were found to have significantly more positive attitudes to dogs than males, but there were no significant differences in the dogs' behaviour either by gender or by attitude.
Keywords: Veterinary students; Dogs; Dog behaviour; New Zealand